Hubungan Mutu Pelayanan Kesehatan dengan Tingkat Kepuasan Pasien di Puskesmas - Nur Qamariyah; Nursyamsiyah Nursyamsiyah (JURNAL FISIOTERAPI DAN ILMU KESEHATAN SISTHANA, 2020)
The quality of health services shows the level of perfection of health services in creating a sense of satisfaction in patients.In this study, researchers used a purposive sampling type of research, namely sampling with special criteria, namely inclusion and exclusion criteria with a cross sectional approach, namely research that explores, analyzes and explains the relationship between the quality of health services and patient satisfaction at the Ridge Health Center. The data needed comes from filling out questionnaires by patients or families of patients seeking treatment at the Ridge Health Center.The sample in this study used 44 respondents who received treatment at the Ridge Health Center. And in this research, the instrument used was a questionnaire with a total of 40 questions.The results of this study show that there is a relationship between the quality of health services, reliability (0.038<0.05), assurance (0.000<0.05), tangibility (0.002<0.05), empathy (0.000<0.05), and responsiveness (0.000 <0.05) with patient satisfaction. The conclusion of this research is that there is a relationship between the quality of health services (reliability, assurance, tangibility, empathy and responsiveness) with patient satisfaction at the Ridge Community Health Center. The advice that researchers can give is that they can evaluate and improve management to improve the quality of service so that patient satisfaction is related to research results, namely the components of speed of administration, patient comfort as well as completeness of medical equipment and accuracy of information so that it is hoped that it can increase patient satisfaction.